Overlaps between industrial informatics and control, data acquisition and management in Big Science - Manduchi, Gabriele (Frontiers in Industrial Engineering, 2024)
Big Science applications require very large infrastructures and often involve different countries in order to achieve important scientific results or to find solutions to the major problems of mankind, such as finding a clean and endless source of energy. Big Science applications represent not only a scientific challenge, but also large engineering applications involving a wide range of technologies shared with other industrial applications. As a consequence there is a significant overlap in technologies and approaches between Big Science and Industry. In this paper, the overlap between Big Science and industrial applications will be presented in more detail under the control perspective, that is, by highlighting the common aspects between industrial informatics and the control, data acquisition and data management in large scientific applications.